MOSQUITO REPELLENT ACTION OF DURANTA PLUMIERI (VERBENACEAE) AGAINST CULEX QUINQUEFASCIATUS - PAYAL MITTAL; MANISH GOSWAMI; MONIKA AIRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the repellent activity of different extracts of Duranta plumieri against mosquito vector Culex quinquefasciatus. Methods: Four different extracts (petroleum ether, chloroform, ethanol, and aqueous) of D. plumieri were evaluated for repellency test against mosquito vector C. quinquefasciatus Say (Diptera: Culicidae) in comparison with diethyltoluamide (DEET), which was used as a positive control. Results: Results showed that chloroform extract was the most effective against mosquito vector even at a low dose. A direct relationship was observed with different concentrations of D. plumieri extract and the repellent activity. Moreover, all the extracts showed highly significant level of repellency as compared to DEET at 10% dosage till 5 h of exposure. Among all of these, chloroform extract showed significant repellency at 5% dosage till 4 h. Conclusion: Chloroform extract of D. plumieri has the potential as an effective mosquito repellent and further studies are needed to isolate the marker compound responsible for this activity.